2017
DOI: 10.1088/1361-6501/aa825a
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound excited thermography: an efficient tool for the characterization of vertical cracks

Abstract: Ultrasound excited thermography has gained a renewed interest in the last two decades as a nondestructive testing technique aimed at detecting and characterizing surface breaking and shallow subsurface discontinuities. It is based on measurement of the IR radiation emitted by the specimen surface to detect temperature rises produced by the heating of defects under high amplitude ultrasound excitation and is primarily addressed to flaws with contacting faces, such as kissing cracks or tight delaminations. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 142 publications
0
17
0
Order By: Relevance
“…Specifically, detection of dental caries at very early stages of formation has proven to be a key application of thermography in biomedicine by providing diagnostic contrast based on enhanced absorption of light at caries [7][8][9], as opposed to other emerging technologies such as Raman spectroscopy [13] and optical coherence tomography (OCT) [14,15], which rely on changes in scattering of light at caries. Appealing, if not unique, characteristics of thermography include: being no-contact, having the ability to inspect opaque [4,[16][17][18][19][20] and turbid materials [7][8][9], and being scalable [3,4]. Moreover, depending on the application, different types of external excitation, such as optical [7], magnetic [17], mechanical waves [19], electrical [4,16] or even cyclic stress/strain [18], can be utilized to induce the thermal wave field inside the sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, detection of dental caries at very early stages of formation has proven to be a key application of thermography in biomedicine by providing diagnostic contrast based on enhanced absorption of light at caries [7][8][9], as opposed to other emerging technologies such as Raman spectroscopy [13] and optical coherence tomography (OCT) [14,15], which rely on changes in scattering of light at caries. Appealing, if not unique, characteristics of thermography include: being no-contact, having the ability to inspect opaque [4,[16][17][18][19][20] and turbid materials [7][8][9], and being scalable [3,4]. Moreover, depending on the application, different types of external excitation, such as optical [7], magnetic [17], mechanical waves [19], electrical [4,16] or even cyclic stress/strain [18], can be utilized to induce the thermal wave field inside the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Appealing, if not unique, characteristics of thermography include: being no-contact, having the ability to inspect opaque [4,[16][17][18][19][20] and turbid materials [7][8][9], and being scalable [3,4]. Moreover, depending on the application, different types of external excitation, such as optical [7], magnetic [17], mechanical waves [19], electrical [4,16] or even cyclic stress/strain [18], can be utilized to induce the thermal wave field inside the sample. A comprehensive review of conventional thermography techniques such as PT and LIT can be found in another paper of this special issue on "Novel Ideas for Infrared Thermography also Applied in Integrated Approaches".…”
Section: Introductionmentioning
confidence: 99%
“…As such, the defects behave like localized heat sources and can be detected with a thermographic system [1]. This makes vibrothermography a promising technique for detection of tightly closed cracks and kissing bonds in composites, especially if the defect interfaces are aligned normal to the inspection surface which is hard to detect using other NDT techniques [2].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…1 LIT, compared to most other NDT techniques, has the advantages of being non-contact, having the ability to inspect opaque [1][2][3][4][5][6] and turbid materials, [7][8][9] and being scalable (e.g., microscopic LIT of leakages in integrated circuits 2 vs. inspection of airplane parts 6 ). Moreover, depending on the application, different types of external excitation, such as optical, 8 electrical, 1,2,10 magnetic, 3 mechanical waves (ultrasound) 5 or even cyclic stress/strain, 4 can be utilized to induce the thermal wave field inside the sample. Due to these promising abilities, LIT has been successfully implemented in research for defect detection and evaluation of broad range of materials, spanning from composite materials, 10 to semiconductor, 11 to biological hard tissues.…”
Section: © 2018 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%